Effects of Cosmetic Formulations Containing Hydroxyacids on Sun-Exposed Skin: Current Applications and Future Developments - Andrija Kornhauser; Sergio G. Coelho; Vincent J. Hearing (Dermatology Research and Practice)
This paper describes recent data on the effects of various skin formulations containing hydroxyacids (HAs) and related products on sun-exposed skin. The most frequently used classes of these products, such as α- and β-hydroxyacids, polyhydroxy acids, and bionic acids, are reviewed, and their application in cosmetic formulations is described. Special emphasis is devoted to the safety evaluation of these formulations, particularly on the effects of their prolonged use on sun-exposed skin. We also discuss the important contribution of cosmetic vehicles in these types of studies. Data on the effects of HAs on melanogenesis and tanning are also included. Up-to-date methods and techniques used in those explorations, as well as selected future developments in the cosmetic area, are presented.